Methodology of Russian soft and hard power impact in Estonia. - Szyłkowska Monika (2022)
Soft power elements can be the so-called persuasive means of political influence (culture, propaganda, diplomacy). The Russian Federation, with its historical legacy, by some historians referred to as the "siege complex", still seems to prefer changes in the distribution of power at the global level, while being aware of the benefits of cooperation with the wider West. Nevertheless, the position regarding some former USSR Republics, which it would most likely see directly in its sphere of influence, seems to remain the same, hence the actions taken and the methodology of conduct have their own characteristic features.